Acetaminophen Overdose as a Potential Risk Factor for Parkinson's Disease. Issue 6 (15th July 2019) - Bohler, Sacha; Liu, Xiaosong; Krauskopf, Julian; Caiment, Florian; Aubrecht, Jiri; Nicolaes, Gerry A. F.; Kleinjans, Jos C. S.; Briedé, Jacco J.
Abstract : Four complementary approaches were used to investigate acetaminophen overdose as a risk factor for Parkinson's disease (PD). Circulating microRNAs (miRNAs) serum profiles from acetaminophen‐overdosed patients were compared with patients with terminal PD, revealing four shared miRNAs. Similarities were found among molecular structures of dopamine (DA), acetaminophen, and two known PD inducers indicating affinity for dopaminergic transport. Potential interactions between acetaminophen and the human DA transporter were confirmed by molecular docking modeling and binding free energy calculations. Thus, it is plausible that acetaminophen is taken up by the dopaminergic transport system into the substantia nigra (SN). A ChEMBL query identified proteins that are similarly targeted by DA and acetaminophen. Here, we highlight CYP3A4, present in the SN, a predominant metabolizer of acetaminophen into its toxic metabolite N‐acetyl‐p‐benzoquinone imine and shown to be regulated in PD. Overall, based on our results, we hypothesize that overdosing of acetaminophen is a potential risk factor for parkinsonism.